Setting sights on new horizons - Abd Razak, Dzulkifli (2010)
MALAYSIA and Cuba created history this week when their leading institutions, Universiti Sains Malaysia (USM) and Finlay Institute respectively, signed a Memorandum of Understanding (MOU), which will facilitate the development of a new, more affordable meningitis vaccine. The MOU was signed at the Malaysian Embassy in Havana and witnessed by guestofhonour Senior Science Adviser to the Cuban Council of State Dr Fidel Castro DiazBalart and Malaysian Ambassador to Cuba Yean Yoke Heng. Prior to this, both institutions have been partners for almost eight years doing various academic and research collaboration on the quiet.